Emotional Attractors in Subject-Verb Number Agreement - Hatzidaki, Anna; Santesteban, Mikel (Frontiers in Psychology, 2022)
Considering the crosstalk between brain networks that contain linguistic as well as emotional information and that no studies have examined the impact of semantic information of affective nature on subject-verb number agreement, the present Event Related Potential (ERP) study investigated the extent to which emotional local nouns whose number mismatched that of subject head nouns might be considered by the parser during comprehension of grammatically correct sentences. To this end, twenty-eight Spanish native speakers were tested on a self-paced reading task while their brain activity was recorded. The experimental materials consisted of 120 sentences where Valence (negative vs. neutral) and Number (singular vs. plural) of the local noun of the singular subject-NP were manipulated; El gorro de aquel/aquellos cazador(es)/mecánico(s) era... (‘The hat of that/those hunter(s)/mechanic(s) was...’). ERP results measured in the local noun position showed that Valence and Number interacted in the 300-500 ms (negative component) and 780-880 ms (Late Positivity) time windows. In the (target) verb position, the two factors only interacted in the late 780-880 ms time window, revealing an “ungrammatical illusion” for plural marked neutral words. Our findings suggest that number agreement is sensitive to affective meaning but that the emotional information of an attractor is considered in different operations and at different stages during grammatical sentence processing: it can affect lexical and syntactic representation retrieval of a subject-NP and impact agreement encoding only at late stages of processing, during verb agreement and feature integration.